System on Chip Design: New Harmonized Master Studies Curriculum in Macedonia and Serbia - Petković, Predrag; Trajanov, Dimitar; Grnarov, Aksenti; Litovski, Vancho (My University, 2009)
The continuous progress of semiconductor technology has made it possible to implement complex systems on a single chip, which has led to new challenges in design methodologies. Driven by these technological forces, the Faculty of Electrical Engineering and Information Technologies (FEIT) – Skopje and Faculty of Electronic Engineering, University of Niš, Serbia with support from TEMPUS JEP_41107_2006 Project have developed an interdisciplinary Master of Science Programme on System-on-Chip design. The programme aims to provide students with competence and skills for designing, analyzing and verifying embedded systems. In this paper, we describe the process of developing the curriculum and the study programme plans.
Keywords: Master studies, Curricula harmonization, System on Chip